2023
DOI: 10.3390/foods12173213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Physical Properties and Volatile Odor Characteristics of Shiitake Mushrooms (Lentinula edodes) in Far Infrared Radiation Drying

Long Xie,
Yu-Si Jiang,
Yu-Bin Wang
et al.

Abstract: The effects of far infrared radiation drying (FID) on physical properties (drying kinetics, color, shrinkage ratio, rehydration ratio, and microstructural characterization) and volatile odor characteristics (volatile odor profile distinction and volatile compounds) of shiitake mushrooms were evaluated in this study. During the FID, the drying time decreased with the increase in drying temperature, and it had a less significant effect in the lower temperature range. The increase in drying temperature led to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In this study, a total of 36 volatile flavor compounds were identified, which differs from previous reports. Qin et al [ 55 ], reported a total of 62 volatile compounds and Xie et al [ 56 ] documented 20 compounds in the fresh L. edodes fruiting body. These discrepancies may arise from various experimental factors, such as the specific strains used, the cultivation substrate, the development stage, and the analytical techniques employed [ 11 , 31 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 36 volatile flavor compounds were identified, which differs from previous reports. Qin et al [ 55 ], reported a total of 62 volatile compounds and Xie et al [ 56 ] documented 20 compounds in the fresh L. edodes fruiting body. These discrepancies may arise from various experimental factors, such as the specific strains used, the cultivation substrate, the development stage, and the analytical techniques employed [ 11 , 31 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hot air drying (HD) is simple and inexpensive, and at the same time facilitates the formation of the characteristic flavor substances in Lentinula Edodes due to enzymatic and Maillard reactions; however, it also leads to a partial loss of nutrients and the appearance of the final product [9]. Compared with hot air drying, Xie et al [10] used infrared radiation drying (ID) technology to dry Lentinula Edodes and found that it not only improved the drying speed but also maintained the quality of Lentinula Edodes. Studies have shown that the high-quality characteristics of products after vacuum freeze drying (VD) are attributed to the low temperature and moisture transfer modes [11].…”
Section: Introductionmentioning
confidence: 99%